Niños en vasijas. Entierros tardíos del Valle Calchaquí (Salta) - Baldini, Lidia; Baffi, Elvira I. (RUNA, archivo para las ciencias del hombre)
In connection with the agglutinated settlement of the Regional Developments Period frequently have registered children burials in ordinary vessels that would be presented in similar proportions to those made in decorated ums and they could connote different situations, the interred individual’s age or their social position, for example. We analyze information published and unpublished on children burials in ordinary vessels in late Calchaquí valley settlements and their treatment from beginnings of the XX century. The analysis it is that the heap of seemingly very big information, it can be scarce, incomplete and contradictory, and that it has not been deepened in certain evidences that they would reveal aspects of the mortuary ritual.